The Theoretical Origin of Adhering to People-Centeredness in Ideological and Political Education in the New Era —An Investigation Based on Marxist Classic Texts - Shuyuan Hao (Lecture Notes in Education Psychology and Public Media, 2026)
The people-centeredness advocated by ideological and political education has profound Marxist theoretical origins, and its core essence is consistent with Marx and Engels' theories on human beings. Adhering to people-centeredness in ideological and political education in the new era represents the dialectical unity of logical starting point and logical destination: taking "free and conscious human beings" as the logical starting point, it requires ideological and political education to respect human subjectivity, conform to human nature and respond to public aspirations; taking the return of human essence and the all-round development of human beings as the logical destination, it requires ideological and political education to take promoting the all-round development of human beings as the fundamental goal and nurture people with advanced ideological theories. Adhering to people-centeredness in ideological and political education in the new era is the dialectical unity of core goal and fundamental goal: taking "theory persuading people" as the core educational goal, it realizes the organic integration of theory and the masses, and turns scientific theory into a material force for transforming the world; taking "the free development of all people" as the fundamental goal, it realizes the organic unity of human all-round development and social development, and highlights the value pursuit of Marxism. Adhering to people-centeredness in ideological and political education in the new era is the dialectical unity of practical path and value orientation: it gives full play to human initiative to realize the harmonious coexistence of human beings and the environment; it persists in focusing on "real individuals" to consolidate the practical foundation of ideological and political education, so that ideological and political education takes root in reality and stays close to the masses.